أهمية صيانة وإصلاح السفن في سوريا - أحمد غالب (Latakia University Journal -Engineering Sciences Series, 2019)
تبين نتائج الإحصاء وجود أكثر من 370 سفينة مملوكة أو مدارة من قبل شركات ملاحية سورية، يندرج أغلبها ضمن سفن البضائع العامة، و يرفع معظمها أعلاماً لدول أجنبية. مع العدد الكبير من السفن المملوكة للسوريين، أصبح من الضروري إيجاد أحواض إصلاح على الشاطئ السوري، بهدف إصلاح السفن السورية وتوفير القطع الأجنبي، إضافة إلى خلق فرص عمل تستوعب اليد العاملة، وفتح مجالات واسعة أمامها لتطوير صناعة بناء وإصلاح السفن. وعند توفر هذه الأحواض والكوادر البشرية المؤهلة، من الممكن إجراء الإصلاح والصيانة للسفن السورية، ولسفن تأتي من دول مجاورة في ظل توفر المكان المثالي لإنشاء أحواض الصيانة، وتوفر الإمكانيات البشرية والمادية للقيام بهذه الصناعة. Statistical results show that there are more than 370 ships which belong to marine companies. Most of them are working for general trading and using the foreign flag states. Since there are many ships which belong to Syrian owners, it is necessary to build a special dock on the Syrian Coast, at least for the maintenance of the Syrian ships. This will save the foreign currency and finds more working opportunities, in addition to making wider fields for ship-building and developing maintenance. This is in addition to more active skilful staffs of workmanship for the Syrian ships and those coming from neighboring countries. This will be verified, if we have the ideal dock for the ship maintenance, building and the required financial and workmanships facilities.